Vertically aligned N-doped CNTs growth using Taguchi experimental design - Silva, Ricardo M.
The Taguchi method with a parameter design L-9 orthogonal array was implemented for optimizing the nitrogen incorporation in the structure of vertically aligned N-doped CNTs grown by thermal chemical deposition (TCVD). The maximization of the I-D/I-G ratio of the Raman spectra was selected as the target value. As a result, the optimal deposition configuration was NH3 = 90 sccm, growth temperature = 825 degrees C and catalyst pretreatment time of 2 min, the first parameter having the main effect on nitrogen incorporation. A confirmation experiment with these values was performed, ratifying the predicted I-D/I-G ratio of 1.42. Scanning electron microscopy (SEM) characterization revealed a uniform completely vertically aligned array of multiwalled CNTs which individually exhibit a bamboo-like structure, consisting of periodically curved graphitic layers, as depicted by high resolution transmission electron microscopy (HRTEM). The X-ray photoelectron spectroscopy (XPS) results indicated a 2.00 at.% of N incorporation in the CNTs in pyridine-like and graphite-like, as the predominant species. (C) 2015 Elsevier B.V. All rights reserved.